Insurer Liability for Medically Related Motor Vehicle Accident Costs in Alberta - Jacobs, Philip; Lier, Douglas; Schopflocher, Donald (Assurances et gestion des risques / Insurance and Risk Management, 2004)
In Alberta, automobile insurers are liable for medical costs of casualties who are not responsible for the accident. There is a levy ($43 million in 1999) but there is also a considerable degree of uncertainty about the amount that should be transferred for medical costs. We conducted an analysis of these costs that included the following data: motor vehicle accident claims for most insurance companies in Alberta in 1999 (which were linked to provincial health insurance registrations); all hospitalizations and emergency room visits in the province that were related to motor vehicle accidents; records (physician, inpatient hospital, outpatient hospital, ambulance, insured drugs) for subsequent one year post accident utilization; and unit administrative costs for health services, set by the province. A second analysis, using 1997 - 2000 data and only hospital inpatient and emergency admissions, was conducted for 3 year utilization experience, and projected beyond. Liability reduction factors were obtained from provincial transportation statistics. Our results indicated that total costs (using administrative prices) amounted to $119 million in 1999 and estimated liability was $82 million. Several areas of uncertainty remained; these included the actual costs beyond three years post - accident, the relationship of administrative prices to actual resource costs; and the roles played in liability by other groups (Workers Compensation and non-insured drivers). This study forms a basis for setting the insurance levy which is more objective than methods used before.